Analisis Ekologi dalam Kumpulan Puisi "Pada Suatu Hari Aku Tidak Mencintaimu Lagi" Karya Adi K. - Novi Rilwita, Rezki; Andriyani, Noni (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Human greed to dominate the earth makes life unstable and the forests are barren. This phenomenon has resulted in many Indonesian writers creating literary works that relate the environment to the theory of ecological literature. Ecological literature is a literary study that discusses the relationship between literature and the universe. The relationship between the two is considered important for research with the formulation, how is the ecological literature in the collection of poems In One Day I Don't Love You Again by Adi K? The theory used is Endraswara's theory with the concepts of pollution, wilderness, disaster, housing/shelter, animals, and earth. The approach used is a qualitative approach with the type of library research. The method used is the descriptive method with the hermeneutic technique. The results of the study show that Adi K's collection of poems One Day I Don't Love You Again contains the concept of ecological literature. The dominant concept that emerges is the earth and housing. Meanwhile, concepts that rarely appear are pollution and disaster. The concepts of ecological literature in this collection of poems are a form of literary criticism carried out by the author. The author expresses feelings through natural events that are happening so that we can protect nature and the surrounding environment.